Efektivitas Pengobatan Tanaman Herbal dan Terapi Tradisional untuk Penyakit Tulang dan Persendian - Cahyaningsih, Erna; Anita Dewi, Ni Luh Kade Arman; Udayani, Ni Nyoman Wahyu; Dwipayanti, Ni Kadek Sari; Megawati, Fitria (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Bones are the body's framework that causes the body to stand upright, where the muscles are attached to allow the passage of blood vessels, where the bone marrow and nerves protect soft tissues. Traditional medicine is an effort to treat or treat other ways outside of medical science or nursing science. Indonesia is one of the countries that have the potential to develop medicinal plant cultivation and use it as an alternative treatment. This study aims to determine the effectiveness of herbal medicine and traditional therapy for bone and joint diseases. This study uses the method of literature study. The results showed that traditional herbal therapy for ball compresses, lemongrass warm compresses, cinnamon warm compresses, lavender aromatherapy warm water flower compresses, bangle rhizome compresses, and ginger warm compresses can be used for bone and joint diseases. Where there are compounds in herbal plants that have effectiveness as traditional medicine and therapy for bone and joint diseases, namely flavonoids, quercetin, curcumin, 6-gingerol and shogaol, alkaloids, steroids, and saponins.